Millie's treasure [large type] - Y'Barbo, Kathleen (Y'Barbo, Kathleen. Secret lives of Will Tucker., 2015)
"The notorious Will Tucker is passing himself off as a British gentleman while he is really seeking a hidden treasure map connected to heiress Millie Cope's family. It's up to Pinkerton agent Kyle Russell to determine if Millie is an accomplice or a victim"--